Knowledge, attitudes and practices regarding cervical cancer prevention at Thulamela Municipality of Vhembe District in Limpopo Province - Dorah U. Ramathuba; Doris Ngambi; Lunic B. Khoza; Nditsheni J. Ramakuela (AOSIS, 2016)
Background: Cervical cancer is a widespread and often fatal disease that affected 1 million women globally in 2005. Not only is it the second most common cancer in women but it was also the second leading cause of cancer deaths, accounting for over 250 000 in 2006. Purpose: The purpose of the study was to assess the knowledge, attitudes and practices regarding cervical cancer prevention among rural women in Vhembe District in Limpopo Province. Methodology: A quantitative descriptive approach was adopted. The quantitative design enabled the discovery of more information by means of direct questioning of a sample of women aged 30 years and older. A convenience sampling was used to select the respondents. Data were analysed using the Statistical Package for Social Sciences. Measures to ensure ethical issues were adhered to. Results: The findings revealed that women lacked knowledge about cervical cancer and preventive methods, and displayed positive attitudes to the use of services if made available as health workers did not adequately inform them about the availability of the services. Conclusion: The awareness of cervical cancer among women in Vhembe District is limited. There is a need to educate and promote awareness of cervical cancer among women to reduce the burden of morbidity and mortality. Keywords: Attitudes, knowledge, practices, cervical cancer